Compact Fiber Optic Trackside Sensor for Rail Vehicle Detection and Analysis. Issue 6 (2018) - Kepak, Stanislav; Cubik, Jakub; Nedoma, Jan; Hruby, David; Hejduk, Stanislav; Zavodny, Petr; Fajkus, Marcel; Vasinek, Vladimir
Abstract: The article describes a system for the trackside detection of rail vehicles based on the fiber-optic interferometer. Besides the phase sensitive distributed systems, the interferometers are the only fiberoptic sensing technology capable of working in indirect contact with the rail while offering similar functionality as track-mounted sensors. The proposed trackside sensor uses the balanced Mach-Zehnder interferometer. The advantage of this type of interferometer is easy multiplexing, low cost and the possibility of flexible sensor design. The article describes the design of a sensor with multiple outputs of 3x3 coupler used for passive phase demodulation. The sensor has been tested on the railway track attached to the railway bridge. Results have shown that train operations can be reliably monitored using the developed system and it allows distinguishing the individual cars or wagon on the closer track.